Synthes of robust quasiinvariant system of active shielding of overhead transmission lines magnetic field - Kuznetsov, B. I.; Bovdui, I. V.; Nikitina, T. B.; Kolomiets, V. V.; Kobilyanskiy, B. B. (Видавництво Львівської політехніки, 2018)
Synthesis of robust quasiinvariant systems of active screening of a magnetic field generated by overhead transmission lines has been developed. The synthesis is based on the solution of a multi-criteria stochastic game, in which the gain vector is calculated on the basis of the Maxwell equations solutions in the quasi-stationary approximation. The equilibrium state of the game is based on the stochastic particles multiagent multiswarm optimization algorithms. An example of synthesis is given and the possibility of reducing the induction of the initial magnetic field to the sanitary standards level and reducing the sensitivity of the system to variations of the plant parameters is shown.
Keywords: overhead transmission lines; power frequency magnetic field; robust active screening system; multicriteria stochastic game; 621.3.01